Beyond the formalist-realist divide : the role of politics in judging - Tamanaha, Brian Z. (Princeton : Princeton University Press, 2010)
According to conventional wisdom in American legal culture, the 1870s to 1920s was the age of legal formalism, when judges believed that the law was autonomous and logically ordered, and that they mechanically deduced right answers in cases. In the 1920s and 1930s, the story continues, the legal realists discredited this view by demonstrating that the law is marked by gaps and contradictions, arguing that judges construct legal justifications to support desired outcomes. This often-repeated historical account is virtually taken for granted today, and continues to shape understandings about jud.
Cover; Title; Copyright; Contents; Acknowledgments; 1 Introduction; PART ONE: THE LEGAL FORMALISTS; 2 The Myth about Beliefs in the Common Law; 3 The Myth about "Mechanical Jurisprudence"; 4 The Holes in the Story about Legal Formalism; PART TWO: The Legal Realists; 5 Realism before the Legal Realists; 6 A Reconstruction of Legal Realism; PART THREE: STUDIES OF JUDGING; 7 The Slant in the "Judicial Politics" Field; 8 What Quantitative Studies of Judging Have Found; PART FOUR: LEGAL THEORY; 9 The Emptiness of "Formalism" in Legal Theory; 10 Beyond the Formalist-Realist Divide; Afterword; Notes.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Judges -- United States; Judicial process -- United States; Law -- Political aspects -- United States; Law -- United States -- Philosophy; Juges -- États-Unis.; Processus judiciaire -- États-Unis.; Droit -- Aspect politique -- États-Unis.; Droit -- États-Unis -- Philosophie; POLITICAL SCIENCE -- Government -- Judicial Branch; LAW -- Legal Services; LAW -- Civil Procedure; LAW -- Jurisprudence; Judges; Judicial process; Law -- Philosophy; Law -- Political aspects; United States; Legal formalism; Legal realism